THE INDONESIAN CLERICS COUNCIL (MUI) AND THE ISSUE OF THE FREEDOM OF RELIGION IN THE CASE OF AHMADIYAH - Rochmat, Saefur (Al-Ulum, 2014)
The Republic of Indonesia does not follow the pure concept of nation state as the national ideology of Pancasila recognizes the role of religion in the national political system. Based on this conception, the government has facilitated the establishment of the ministry of religious affairs which often breaks the principle of religion freedom. In the case of Islamic sect of Ahmadiyah, MUI, established under the auspice of the ministry of religions, has accused the Islamic sect of Ahmadiyah of having done the act of blasphemy. Actually, this will not become a problem if the state consistently applies the separations of power between public and private affairs. In this regard, religious communities take in a role of civil society which would provide checks and balances to the government in the pursuance of democracy. In line with this, the ministry of religious affairs, by means of MUI, should not judge people based on their beliefs. Al-Qurâan also recognizes the existence of different religions as well as some sects within a certain religion. Moreover, it is useful to implement Richard Niebuhrâs theory of denomination. Last but not least, MUI should act following the concept of nation state in order to moderate power which tends to corrupt. -----Republik Indonesia didirikan berdasarkan dasar negara Pancasila. Sejalan dengan itu, negara memfasilitasi pendirian kementerian agama, yaitu sebuah institusi yang sering melanggar pinsip kebebasan beragama. Sebagai contoh, MUI, yang didirikan di bawah naungan kementerian agama, menuduh Ahmadiyah, salah satu aliran dalam Islam, telah melakukan penistaan agama. Sebenarnya, model negara Pancasila tidak bermasalah bila negara secara konsisten menerapkan pemisahan kekuasaan antara urusanÂ  publikÂ  dan urusanÂ  privat. Dalam hal ini organisasi-organisasi keagamaan, seperti Ahmadiyah dan MUI, memainkan peran sebagai unsurÂ  civil society, dalam arti menjadi penyeimbang bagi negara, demi terciptanya masyarakat yang demokratis. Oleh karena itu, MUI, tidak menilai orang berdasarkan keyakinannya, karena. al-Qurâan mengakui keberadaan beberapa agama dan aliran-alirannya. Â MUI perlu menilainya berdasarkan teori denominasi karyaÂ  Richard Niebuhr. MUI juga perlu memposisikan diri sebagai bagian dari civil society, mengkritisi penguasa yang cenderung menyalahgunakan kekuasaan.Â